2016
DOI: 10.1369/0022155416679638
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans-Retinoic Acid Augments the Histopathological Outcome of Neuroinflammation and Neurodegeneration in Lupus-Prone MRL/lpr Mice

Abstract: Recently, we demonstrated that treatment with all- trans-retinoic acid (tRA) induced a paradoxical effect on immune activation during the development of autoimmune lupus. Here, we further describe its negative effects on mediating neuroinflammation and neurodegeneration. Female MRL/lpr mice were orally administered tRA or VARA (retinol mixed with 10% tRA) from 6 to 14 weeks of age. Both treatments had a significant effect on brain weight, which correlated with histopathological evidence of focal astrogliosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…For instance, supplementation of RA can ameliorate some tissues’ pathologies, as in the kidney during lupus nephritis, while deteriorating other tissue pathologies, for instance, the lung and skin lesions [ 82 ]. Similarly, RA treatment exacerbates neuroinflammation by increasing autoantibodies, total IgG, and complement C3 protein deposition in the brain tissue and has been associated with more severe neurodegeneration in MRL/lpr mice [ 83 ]. Furthermore, with its potential toxicity [ 84 , 85 ], employing RA as a potential therapeutic for autoimmune disorders requires a deeper consideration for the context in which RA interplays.…”
Section: Efficacies Of Ra In the Treatment Of Autoimmune Diseasesmentioning
confidence: 99%
“…For instance, supplementation of RA can ameliorate some tissues’ pathologies, as in the kidney during lupus nephritis, while deteriorating other tissue pathologies, for instance, the lung and skin lesions [ 82 ]. Similarly, RA treatment exacerbates neuroinflammation by increasing autoantibodies, total IgG, and complement C3 protein deposition in the brain tissue and has been associated with more severe neurodegeneration in MRL/lpr mice [ 83 ]. Furthermore, with its potential toxicity [ 84 , 85 ], employing RA as a potential therapeutic for autoimmune disorders requires a deeper consideration for the context in which RA interplays.…”
Section: Efficacies Of Ra In the Treatment Of Autoimmune Diseasesmentioning
confidence: 99%
“…Interestingly, pre‐injury administration of ATRA reduced infarction volume after experimental stroke and improved neurological outcome and integrity of the BBB (Li et al, 2017, 2018). To some degree, the beneficial effects of ATRA have been attributed to its anti‐inflammatory actions (Behairi et al, 2016; Choi et al, 2009; Theus, Sparks, Liao, Ren, & Luo, 2017). Indeed, several in vitro studies showed that ATRA suppressed inflammatory responses of microglia and astrocytes (Dheen, Jun, Yan, Tay, & Ling, 2005; van Neerven et al, 2010; Xu & Drew, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Progressive Glomerulonephritis With tRA Pre-treatment in Pristane-Induced Lupus tRA treatment of lupus-prone MRL/lpr mice showed paradoxical effects on renal inflammation vs. other tissue pathologies including inflammation of the skin, lungs 12, and neuroinflammation (13), suggesting that tRA can expand the pre-existing immunogenic environment in extrarenal organs in genetically prone lupus. In this study, we further hypothesized that the effects of tRA on lupus disease were disease stage-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Even though retinoid treatment in combination with immunosuppressive drugs showed beneficial effects on lupus nephritis (11), previous findings from our group showed that tRA has paradoxical implications on renal inflammation vs. other tissue pathologies. tRA supplementation during active disease aggravated pathologies in non-renal tissues including skin, lungs (12), and brain (13). These findings indicate that tRA may act as an adjuvant to exacerbate the pre-existing, extrarenal inflammation in individuals genetically prone to develop lupus.…”
Section: Introductionmentioning
confidence: 85%